2014
DOI: 10.1002/oby.20756
|View full text |Cite
|
Sign up to set email alerts
|

From modeling to measurement: Developmental trends in genetic influence on adiposity in childhood

Abstract: ObjectiveEvidence of increasing heritability of BMI over childhood can seem paradoxical given longer exposure to environmental influences. Genomic data were used to provide direct evidence of developmental increases in genetic influence.MethodsBMI standard deviation scores (BMI-SDS) at ages 4 and 10 were calculated for 2,556 twin pairs in the Twins Early Development Study. Twin analyses estimated heritability of BMI-SDS at each age and the longitudinal genetic correlation. One randomly selected twin per pair w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 36 publications
7
29
0
Order By: Relevance
“…The increasing association between the GRS and BMI from birth to 5 years (Fig. S2) is consistent with the observation that the genetic influence on BMI becomes stronger with age over childhood . Epidemiologic studies have shown that rapid early weight gain predicts later obesity and metabolic diseases .…”
Section: Discussionsupporting
confidence: 87%
“…The increasing association between the GRS and BMI from birth to 5 years (Fig. S2) is consistent with the observation that the genetic influence on BMI becomes stronger with age over childhood . Epidemiologic studies have shown that rapid early weight gain predicts later obesity and metabolic diseases .…”
Section: Discussionsupporting
confidence: 87%
“…As children age and they become less dependent on their parents, the genetic effect on energy and macronutrient intakes appears to intensify, as suggested by findings in 11-to 13-year-old US twins (31 to 48 %) (8) . This pattern is similar to other health-related phenotypes, including BMI (15) , which has been recently confirmed through a more complex longitudinal genome-wide complex trait analysis for determining DNA-based heritability (16) . Heritability of dietary energy and macronutrients in adults has been found to vary widely: for energy (32 to 65 %); for fats (35 to 53 %); carbohydrates (25 to 67 %); and proteins (28 to 70 %) (6,11,12,14) .…”
Section: Heritability Of Energy and Macronutrient Intakessupporting
confidence: 74%
“…A recent meta-analysis of the heritability of BMI derived from twin studies concluded that estimates are higher in countries with higher gross domestic product (again, by inference have a more 'obesogenic' environment), and in samples with a higher average BMI [29]. We, along with others have shown that the heritability of BMI increases steadily from early childhood to late adolescence, which could reflect increasing exposure to the 'obesogenic' environment [29,30]. The findings from twin studies have been supported by molecular genetic studies, with evidence that the effects of FTO [31] and a polygenic obesity risk score [32] on BMI are significantly stronger for those born later, suggesting that genetic effects are moderated by environmental exposure.…”
Section: Gene-environment Interplay In the Development Of Obesitymentioning
confidence: 50%